The Implication of Good Governance in Elevating Muzaki's Loyalty to the Islamic Philantrophy Organizations in Salatiga City and Semarang Regency, Indonesia - Tri Wahyu Hidayati (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2022)
This research aims to measure and empirically examine the impact of good governance and understanding of the teachings of ZIS (zakat, infaq, and sadaqah) on Muslims loyalties to the zakat institutions in Salatiga City and Semarang Regency. This research is a quantitative model that employs a questionnaire to gather the primary source for the research variables. The population of this research is muzaki in both areas, and the samples were taken from 94 respondents who regularly deliver their zakat, infaq, and sadaqah through a zakat institution. This study concludes that, firstly, implementing good governance on zakat institutions significantly influences the loyalty of Muslims to zakat institutions in Salatiga and Semarang; hence, the first hypothesis is accepted. Secondly, understanding of teachings on ZIS does not influence the loyalty of Muslims to zakat institutions in Salatiga and Semarang; hence, the second hypothesis is rejected. Third, implementing good governance and understanding of teachings on ZIS influence simultaneously the loyalty of Muslims to zakat institutions in Salatiga and Semarang, so the third hypothesis is accepted. This study notes that the dominant factors influencing muzaki's loyalty arise from external aspects (implementation of good governance), not internal (understanding, piety, and social relations). This research highly recommends that either BAZNAS or LAZ should develop their quality of zakat management systems to encourage Muslims to deliver ZIS through zakat institutions. Thus, zakat funds can be maximally empowered and contribute to the welfare of society.